Identifying cooperation for innovation1em1pta comparison of data sources - Michael Fritsch; Mirko Titze; Matthias Piontek (Industry and Innovation, 2020)
The value of social network analysis is critically dependent on the comprehensive and reliable identification of actors and their relationships. We compare regional knowledge networks based on different types of data sources, namely, co-patents, co-publications, and publicly subsidized collaborative R&D projects. Moreover, by combining these three data sources, we construct a multilayer network that provides a comprehensive picture of intraregional interactions. By comparing the networks based on the data sources, we address the problems of coverage and selection bias. We observe that using only one data source leads to a severe underestimation of regional knowledge interactions, especially those of private sector firms and independent researchers.
Keywords: O30; R12; R30; 330; Knowledge interactions; social network analysis; regional innovation systems; data sources; R&D cooperation